2019
DOI: 10.1093/mnras/stz3287
|View full text |Cite
|
Sign up to set email alerts
|

A two-fluid model for black-hole accretion flows: Particle acceleration, outflows, and TeV emission

Abstract: The multi-wavelength spectrum observed from M87 extends from radio wavelengths up to TeV γ-ray energies. The radio through GeV components have been interpreted successfully using SSC models based on misaligned blazar jets, but the origin of the intense TeV emission detected during flares in 2004, 2005, and 2010 remains puzzling. It has been previously suggested that the TeV flares are produced when a relativistic proton jet originating in the core of M87 collides with a molecular cloud (or stellar atmosphere) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Hence, the outflows/jets are expected to carry a fraction of the available energy (equivalently core emission) at the PSC, which in general considered as the base of the outflows/jets (Chakrabarti 1999;Chattopadhyay & Das 2007;Das & Chattopadhyay 2008;Singh & Chakrabarti 2011;Sarkar & Das 2016). Becker and his collaborators showed that the energy extracted from the accretion flow via isothermal shock can be utilized to power the relativistic particles emanating from the disc (Le & Becker 2005;Becker, Das, & Le 2008;Das, Becker, & Le 2009;Lee & Becker 2020). Moreover, magnetohydrodynamical study of the accretion flows around the black holes also accounts for possible role of shock as the source of high energy radiation (Nishikawa et al 2005;Takahashi et al 2006;Hardee, Mizuno, & Nishikawa 2007;Takahashi & Takahashi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the outflows/jets are expected to carry a fraction of the available energy (equivalently core emission) at the PSC, which in general considered as the base of the outflows/jets (Chakrabarti 1999;Chattopadhyay & Das 2007;Das & Chattopadhyay 2008;Singh & Chakrabarti 2011;Sarkar & Das 2016). Becker and his collaborators showed that the energy extracted from the accretion flow via isothermal shock can be utilized to power the relativistic particles emanating from the disc (Le & Becker 2005;Becker, Das, & Le 2008;Das, Becker, & Le 2009;Lee & Becker 2020). Moreover, magnetohydrodynamical study of the accretion flows around the black holes also accounts for possible role of shock as the source of high energy radiation (Nishikawa et al 2005;Takahashi et al 2006;Hardee, Mizuno, & Nishikawa 2007;Takahashi & Takahashi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The sub-Keplerian flow can give many types of the advective solutions depend on the variation of the AM distributions in the flow. Two types of the advective solutions for the hot accretion flow are very popular in the literature, one, the shocked accretion flow (Fukue 1987;Chakrabarti 1989;Molteni et al 1996;Lanzafame et al 1998;Mukhopadhyay 2003;Becker et al 2008;Das & Czerny 2012;Giri & Chakrabarti 2013;Das et al 2014;Lee et al 2016;Kumar & Chattopadhyay 2017;Dihingia et al 2019;Lee & Becker 2020;Garain et al 2020) and the other, a special kind of the smooth solution known as the Advection-Dominated Accretion Flow (ADAF) solution (Ichimaru 1977;Narayan & Yi 1994;Honma 1996; Narayan et al 1997;Lu et al 1999;Kato et al 2008;Narayan et al 2012;Yuan & Narayan 2014;Kumar & Gu 2018. Interestingly, both the advective disk solutions/models can be generated from the same set of the fluid differential equations and assumptions, but both (shock and ADAF) solutions have basic difference of AM distribution.…”
Section: Introductionmentioning
confidence: 99%